Legal Protection of E-Commerce Consumers’ Personal Data Under Indonesian Law - Mansawan, Isak Semuel Kejne; Sassan, Jonhi; Bernard, Jefri (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The protection of consumer personal data within Indonesia’s digital ecosystem remains a critical challenge, particularly following the enactment of Law No. 27 of 2022 on Personal Data Protection (PDP Law). This study aims to examine the implementation of the PDP Law from three key perspectives: government oversight, compliance among e-commerce business actors, and consumer legal awareness. Employing a combined normative and sociological legal approach, the study utilizes literature review as its primary data collection method. The findings reveal three primary impediments to effective implementation: the absence of an independent supervisory authority, the largely formalistic compliance of digital business entities, and the low level of legal literacy among consumers regarding their personal data rights. The study also highlights potential overlaps with provisions in the Electronic Information and Transactions (ITE) Law, particularly in terms of jurisdiction and enforcement mechanisms. In conclusion, without robust institutional support and comprehensive public legal education, the PDP Law risks becoming ineffective in safeguarding consumer privacy and ensuring meaningful personal data protection in the digital age.